2021
DOI: 10.1088/2053-1591/abf27f
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for the stable existence of γ’ phase and strengthening mechanism of GH4720Li nickel-based superalloy

Abstract: The characteristics of γ′ phase in forgings and heat treatment of GH4720Li superalloy were investigated under a transmission electron microscope by thermal deformation tests under gradient heating process. The experimental results show that there are Cr–Co rich region around the γ′ phase after forging and heat treatment, which guarantees the stable existence of the γ′ phase in the matrix and provides the first barrier to prevent dislocations from cutting the γ′ phase. Therefore, the stable existence of primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The main method of strengthening the alloy was through the precipitation strengthening of the γ′ phase The performance of the alloy is heavily influenced by the quantity, distribution, and siz of the γ′ phase within it. In the research on strengthening GH4720Li alloy [37][38][39], tw types of coupling cutting relationships were observed between the γ′ phase and disloca tions: strong coupling dislocation cutting and weak coupling cutting, depending o…”
Section: γ′ Phase Evolution In Nickel-based Superalloysmentioning
confidence: 99%
See 1 more Smart Citation
“…The main method of strengthening the alloy was through the precipitation strengthening of the γ′ phase The performance of the alloy is heavily influenced by the quantity, distribution, and siz of the γ′ phase within it. In the research on strengthening GH4720Li alloy [37][38][39], tw types of coupling cutting relationships were observed between the γ′ phase and disloca tions: strong coupling dislocation cutting and weak coupling cutting, depending o…”
Section: γ′ Phase Evolution In Nickel-based Superalloysmentioning
confidence: 99%
“…The performance of the alloy is heavily influenced by the quantity, distribution, and size of the γ ′ phase within it. In the research on strengthening GH4720Li alloy [37][38][39], two types of coupling cutting relationships were observed between the γ ′ phase and dislocations: strong coupling dislocation cutting and weak coupling cutting, depending on whether the particle size of the γ ′ phase was greater than or equal to 40 nm. It has been found that the optimum particle size for the γ ′ phase in the best precipitation strengthening state is 40 nm.…”
Section: γ ′ Phase Evolution In Nickel-based Superalloysmentioning
confidence: 99%